Adolescent Interpersonal Communication Culture in Jakarta High School in the Smartphone Era - Ondy Ondy (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Using smartphones in interpersonal communication among adolescents is now commonplace. Many teenagers who follow the flow of communication media in technology choose smartphones as a more effective interpersonal communication medium. Compared to other forms of communication, interpersonal communication occurs personally, in face-to-face situations, and through media. Interpersonal communication is fundamental since it permits it to require place dialogic communication. Exchange may be a shape of interpersonal communication that appears in the event of interaction. Those included in this communication frame are double-functioning, each being the speaker and the audience, on the other hand. This report analyzes adolescents’ interpersonal communication culture in the smartphone-use era based on this statement. The method used is the phenomenological method. The conclusion of this study indicates that the current adolescent interpersonal communication culture is more influenced by digital technology than direct interaction. Therefore, efforts are needed to foster awareness of the importance of maintaining a healthy quality of interpersonal communication amid technological advances.